Thematic features of Kazakh humors (Eurasian Journal of Philology Science and Education, 2016)
Article considers and shows features of classification on theme groups depending between whom the humour is conducted. As, the Kazakh humour exists together with society, and it is considered the phenomenon, flexible to a current of time, to changes, in the article the humour place in the Kazakh culture, national and thematic features is investigated.Ridiculous statements of great people, poets, writers are grouped in such subjects as traditions, the social status, science and education, age features of people, their pertinent humours are analyzed as the examples. Besides, humour in the relative, family relations, humour between the nations, humour between friends and mates, are also grouped in theme groups depending on the national directions.
Keywords: humour; tradition; science and education; social conditions; age feature.